Optimisation of water-in-oil microemulsion formulation stabilised by nonylphenol ethoxylated phosphate ester - Focke, Walter Wilhelm (University of Pretoria, 2013)
Dissertation (MSc (Chemistry))--University of Pretoria, 2007.